Design and Synthesis of Oligoamide‐Based Double α‐Helix Mimetics (Eur. J. Org. Chem. 17/2013). Issue 17 (6th June 2013) - Kulikov, Oleg V.; Thompson, Sam; Xu, Hai; Incarvito, Christopher D.; Scott, Richard T. W.; Saraogi, Ishu; Nevola, Laura; Hamilton, Andrew D.
Abstract : The cover picture shows the binding of transcription factors to nucleic acids. Top left: multicomponent protein; bottom right: leucine zipper; centre: bis‐oligobenzamide peptidomimetic; background: DNA chains. The xanthene‐linked bis‐oligobenzamide shown in the centre is an example of a super‐secondary structural protein mimic. This work details the synthesis of oligobenzamide and oligopyridylamide strands connected through various spacers, allowing tuning of the inter‐helix angle and thus the potential nucleic acid or protein binding properties. Details are discussed in the article by A. D. Hamilton et al. onpage 3427 ff. Dr. Karl Harrison (Department of Chemistry, University of Oxford) is gratefully acknowledged for the production of the cover picture.